The effect of the Islam of the Sahabi after his apostasy on his Companions: Theoretical study - Al-Sallami, Shami Yahia Saeed (Journal of Islamic Sciences, 2020)
This study aimed to demonstrate the extent of the impact of apostasy on the continuation of companionship, in the case of those who were proven to be of them and converted, then converted to Islam, but his conversion to Islam was after the death of the Prophet, may God bless him and grant him peace.After the introduction, the research was organized into the research problem, the importance of the topic, the reasons for choosing it, previous studies, and the research plan, which consisted of an introduction, two studies, and a conclusion, and included: the most prominent results, the most important recommendations, and an index of references, then after the plan came the research methodology used in The study, which was based on the three scientific approaches, the inductive, analytical and deductive approach.One of the most prominent features of the research was to come up with a ruling on this important issue, and to explain the consequences of this ruling, and to link the science of hadith, the science of jurisprudence, and its origins, through the main issue in the research, which is the deterrence of acting in apostasy, from its lack of despair.
Keywords: the companions; justice; apostasy; companionship